Pengaruh Terapi Musik dan Aromaterapi Terhadap Nyeri Persalinan di Pontianak - Sudarto, Sudarto; Rahayu, Halina; Amandus, Amandus; Rangkuti, Winnellia Fridinasandy; Ardiansyah, Fakrul (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT Labor pain is a significant issue experienced by mothers during childbirth, leading to excessive fear and worry for both the mother and her family. If not addressed properly, it can jeopardize the health of both the mother and the fetus, prompting healthcare providers to seek alternative therapies. The combination of aromatherapy relaxation therapy and music therapy is an alternative non-pharmacological therapy for relieving normal labor pain. To analyze the effectiveness of the combination therapy of aroma therapy relaxation and aromatherapy on pain during the active phase of normal delivery. This study utilized a quasi-experimental design with two groups. The study involved a total of 60 mothers in the delivery rooms of Siantan Hilir Health Center and GG Sehat Health Center in Pontianak City. A pre-test and post-test nonequivalent control group design approach was employed, with data analysis conducted using the Wilcoxon test. The results of the study indicated that the intervention group had a p-value of 0.0001 < 0.05 and the control group had a p-value of 0.001 < 0.05, indicating a difference in pain levels before and after the treatment. Based on the results of the Mann-Whitney U Test, a p-value of 0.001 < 0.05 was obtained, indicating a difference in pain intensity between the group of mothers who received a combination of aromatherapy and back massage and the group of mothers who received deep breathing relaxation. Aromatherapy and aroma therapy are effective in reducing normal labor pain during the active phase. It is hoped that these therapies can be considered as alternative techniques for providing relaxation as part of the standard operating procedure for maternal care during the active phase, especially for reducing the intensity of pain during the active phase of normal delivery.  Keywords: Labor Pain, Combination Therapy, Aromatherapy, Active Phase Of Labor  ABSTRAK Nyeri persalinan merupakan masalah  dirasakan oleh ibu waktu melahirkan yang berakibat  menimbulkan rasa takut dan khawatir yang berlebihan bagi ibu maupun keluarganya. Jika tidak diatasi dengan tepat makakesehatan ibu dan janin akan terancam, sehingga petugas kesehatan  mencari terapi alternatif untuk mengatasinya. Kombinasi terapi relaksasi Aromaterapi dan terapi musik alternatif terapi non farmakologi untuk relaksasi mengatasi  nyeri persalinan normal. Menganalisis efektifitas  terapi  kombinasi  relaksasi aroma terapi  dan Aroma terapiterhadap  nyeri  Inpartu kala 1 fase aktif persalinan normal . Penelitian ini menggunakan design quasi-eksperimen dua group. Dengan jumlah sampel 60  ibu  di ruang besalin Puskesmas Siantan Hilir dan Puskesmas GG Sehat Kota Pontianak.Pendekatan pre test and post test nonequivalent control group design dimana peneliti tidak melakukan randomisasi, Analisa data dengan uji Wilcoxon. Hasil uji  menunjukkan bahwa kelompok intervensi  nilai ρ 0,0001 < 0,05 dan kelompok kontrol  nilai ρ 0,001 < 0,05 yang berarti ada perbedaan tingkat nyeri sebelum dan sesudah perlakuan. Berdasarkan hasil uji statistik Mann Whitney U Test diperoleh nilai ρ 0,001 < 0,05 maka dapat  diartikan ada perbedaan intesitas nyeri  pada kelompok ibu melahirkan yang mendapat perlakukan kombinasi  aromaterapi dan pijat pungung  dengan kelompok ibu yang medapatkan realaksasi nafas  dalam. Terapi aroma dan Aroma terapi efektif untuk menurunkan nyeri persalian normal pada kala satu fase aktif .Diharapkan dapat dijadikan bahan alternatif untuk memberikan teknik relaksasi  sebagai SOP  dalam memberikan asuhan sayang ibu pada fase aktif  khususnya untuk menurunkan intensitas nyeri   pada inpartu kala I fase aktif persalinan normal. Kata Kunci: Nyeri Persalinan, Terapi Kombinasi, Aromaterapi, Fase Aktif Persalinan